2021
DOI: 10.1002/ece3.8434
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive phylogeography of the widespread pond snail genus Radix revealed restricted colonization due to niche conservatism

Abstract: To clarify the effect of niche conservatism on evolutionary history, we focused on freshwater snails, which have different ecological and phylogenetic properties from previously tested taxa. We conducted a phylogenetic analysis using 750 lymnaeid individuals from 357 sites of eleven Radix species. Then, we estimated the ancestral distribution using the geographic coordinates and colonization routes. In addition, a statistical test of the colonization distances in the latitudinal and longitudinal directions was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 116 publications
(163 reference statements)
0
1
0
Order By: Relevance
“…How R. rufescens colonized Wadi Tiwi remains enigmatic. One of the excellent maps of Saito et al (2021) we have completed with our finding (Fig. 5).…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…How R. rufescens colonized Wadi Tiwi remains enigmatic. One of the excellent maps of Saito et al (2021) we have completed with our finding (Fig. 5).…”
Section: Discussionsupporting
confidence: 63%
“…The evolutionary history of Radix and main colonization routes are well known (Saito et al 2021). The first diversification area was situated in east India, the rufescens/natalensis group split then into two lines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that temperature differences between the native range and introduced areas were important in maintaining populations during the early stages of the invasion. In general, temperature can be a major factor determining the success or failure of an alien species introduction and establishment (Hayes & Barry, 2008;Petitpierre et al, 2012;Guisan et al, 2014), and it has also been suggested that niche conservatism for temperature may influenced the formation of the distribution of Hygrophila snails (Saito et al, 2021).…”
Section: Origins Of Gyraulus Chinensis Invasionmentioning
confidence: 99%